Journal of big history - International Big History Association (International Big History Association, 2017)
Big History seeks to understand the integrated history of the Cosmos, Earth, Life, and Humanity, using the best available empirical evidence and scholarly methods.
Keywords: Cosmology : Periodicals; World history : Periodicals; Human evolution : Periodicals; Cosmology; Human evolution; World history; Earth (Planet) : History : Periodicals; Earth (Planet)